Socialization' phenomenas of modern adolescents: Pro et contra - E.N. Volkova (Социальная психология и общество)
Context and Relevance. Digital socialization is associated with a number of new phenomena – computer games, cyberbullying, hacking, Net-friendship, phubbing, digital self-harm. Current understanding and research interest to these phenomena varies, especially in Russian publications. These phenomena share similar cause-and-effect relationships, determinants, factors of emergence and development, so they may represent elements of the general socialization process of modern adolescents. Objective. Problematization of the ambivalence of new phenomena – passion for computer games, cyberbullying, hacking, Net-friendship, phubbing, digital self-harm – in the context of socialization of modern adolescents. Conclusions. Phenomena of digital socialization of modern adolescents have common features due to mutual integration of virtual and real-life environments. Trends in the prevalence of the phenomena of digital socialization of teenagers are different and are influenced by the development of digital technologies. Adults’ behavior models the attitudes to digital technologies and their behavior in hybrid reality is a condition for the quality of outcomes of digital socialization of modern adolescents. One of the important factors for predicting the outcomes of socialization is the screen time as a parameter that reflects the amount and filling of time in the life. Adolescents and adults perceive the new phenomena differently: adults consider socialization to be successful according to some criteria, and adolescents – according to others. The adolescent socialization depends on the ability of adults to act as agents of socialization influences. Studies of the developmental possibilities of computer games, as well as protective factors against cyberbullying, hacking, and digital self-harm are related to the parental control, parental attention to adolescents, parenting styles, parental attachment.